An Investigation Into Safe Printmaking Methods With Etching Without Acid, For Art & Design For Higher Education Institutions In Pakistan - Khan, Fazal Ellahi; Power, Nigel (Idealogy Journal; Vol 7 No 1 (2022): Idealogy Journal (April 2022)DO - 10.24191/idealogy.v7i1.314, 2022)
The purpose of this research was to explore healthy, environmentally friendly, effective, and economical alternatives to traditional acid-base printmaking practices. The research took place in Pakistan, where chemicals and acids are widely used for printmaking in Art & Design higher education institutions as well as in artist’s workshops. These approaches pose serious health and safety issues for teachers, students, and practitioners alike as well as causing environmental damage. However, no research on safer alternatives had been previously carried out in the country. The investigation filled this gap using a mixed-methods research design: a practice-led project focused on the design, development, and testing of an electro-etching machine made entirely from economical and locally available components; the opinions and ideas of experts and practitioners were gauged through questionnaires and structured interviews; and, finally, the technical and aesthetic qualities and possibilities of the proposed machine were tested and evaluated through a print workshop involving students, professors, and print artists. The research found that the proposed method met the inquiry’s main objectives, namely: to produce high-quality artistic prints using a safe and economical alternative to acid. The researchers conclude by arguing that the research has the potential to move educational and artistic practices in Pakistan away from unhealthy and damaging methods and towards safe and sustainable forms of print production. Keywords: Printing acid free; Health and safety; Electro etching; Sustainibility.